An Asymmetric Analysis of the Relationship between Openness and Inflation in Côte d’Ivoire - Kouton, Jeffrey (International Journal of Economics and Financial Issues, 2018)
This study investigates the existence of an asymmetric relationship between openness and inflation in Côte d’Ivoire from 1970 to 2015. For that purpose, a Non-linear Autoregressive Distributed Lags model is implemented. The KOF Globalization index is used to measure openness. We decompose the index in negative and positive partial sums and in quantiles partial sums. The results suggest both short and long runs asymmetries in the relationship between openness and inflation in Côte d’Ivoire. In the long run, inflation strongly responds to a decrease in openness than to an increase in openness. In the short run, the asymmetric effect of openness on inflation is time-specific. Furthermore, a positive and significant effect of openness on inflation is found for low values of openness. For median values of openness, the effect on inflation is negative. For high values of openness, the effect on inflation is positive but non-significant. Keywords: Asymmetry, Inflation, Openness. JEL Classifications: C01, E31, F41 DOI: https://doi.org/10.32479/ijefi.7095